Antigen-Specific IFN-γ Responses Correlate with the Activity of M. tuberculosis Infection but Are Not Associated with the Severity of Tuberculosis Disease - Irina Yu. Nikitina; Alexander V. Panteleev; Ekaterina V. Sosunova; Natalya L. Karpina; Tatef R. Bagdasarian; Irina A. Burmistrova; Sofia N. Andreevskaya; Larisa N. Chernousova; Irina A. Vasilyeva; Irina V. Lyadova (Journal of Immunology Research)
IFN-γ is a key cytokine in antituberculosis (TB) defense. However, how the levels of its secretion affect M. tuberculosis (Mtb) infection is not clear. We have analyzed associations between IFN-γ responses measured in QuantiFERON®-TB Gold In-tube (QFT) assay, TB disease severity, and Mtb infection activity. TB severity was evaluated based on the results of radiological, microbiological, and clinical examinations. Antigen-driven IFN-γ secretion did not correlate with TB severity. Mitogen-induced IFN-γ secretion correlated inversely with the form of pulmonary pathology and the area of affected pulmonary tissue; the levels of spontaneous IFN-γ secretion correlated with patients’ age (r = 0.395, p = 0.001). Mtb infection activity was evaluated based on radiological data of lung tissue infiltration, destruction, dissemination or calcification, and condensation. The rate of positive QFT results and the levels of antigen-driven IFN-γ secretion increased in a row: patients with residual TB lesions < patients with low TB activity < patients with high TB activity. Thus, antigen-driven IFN-γ secretion and QFT results did not associate with TB severity but associated with the infection activity. The results suggest that quantitative parameters of IFN-γ secretion play a minor role in determining the course of TB disease but mirror the activity of the infectious process.